Facial reactions during emotion recognition in borderline personality disorder: a facial electromyography study - Matzke, Burkhard; Herpertz, Sabine; Berger, Christoph; Fleischer, Monika; Domes, Gregor (Psychopathology, 2014)
Background: Previous studies have suggested increased sensitivity for emotional facial expressions and subtle impairments in emotion recognition from facial expressions in borderline personality disorder (BPD). It has been proposed that facial mimicry contributes to emotion recognition of and emotional response to facial expressions. This study investigated whether BPD patients differ in facial reactions, emotion recognition and their subjective emotional response to faces showing different emotional expressions. Method: Twenty-eight female BPD patients and 28 healthy controls underwent a facial recognition task with dynamic facial pictures while facial muscle activity (occipitofrontalis, corrugator supercilii, levator labii superioris, zygomaticus major and orbicularis oculi) was recorded. Furthermore, participants rated the emotional intensity of the presented faces and the intensity of their subjective feeling of this emotion. Results: Compared to controls, BPD patients showed enhanced responses of the corrugator supercilii muscle in response to angry, sad and disgusted facial expressions, and attenuated responses of the levator labii superioris in response to happy and surprised faces. There were no overall group differences regarding emotion recognition performance or intensity ratings. Conclusion: These results do not support the view that facial recognition in BPD is impaired or that there is a general hypersensitivity to the emotional state of others. Instead, they suggest a negativity bias in BPD, expressed by reduced facial responding to positive social signals and increased facial responding to negative social signals. This is a pattern of facial reactions that might contribute to the difficulties in social interactions frequently reported by patients with this disorder.